Սնանկություն. տնտեսաիրավական կարգավորման և կառավարման որոշ հիմնախնդիրներ - Սարգսյան Վարսենիկ (Bulletin of Yerevan University G: Economics, 2017)
The article presents the main prerequisites of the insolvency of the RA organizations and examines the main provisions of economic and legal regulation of bankruptcy. Identifying some of the key issues of bankruptcy prevention and management, it outlines the main mechanisms of bankruptcy regulation and shows the most comprehensive solutions to the problem. The latter are based on the localization of the best international experience, taking into account the specifics of the settlement of the bankruptcy process in RA.